PRESENCE AND INOCULUM DENSITY OF Phytophthora IN, DIFFERENT COCONUT CULTIVARS IN DAVAO, PHILIPPINES - N.C.S.J. Bachiller (International Coconut Community, 2004)
Phytophthora palmivora was present in the soil samples and organic debris deposited in leaf axil of coconut. Block planted with CAMT x MRD hybrid had the highest number of Phytophthora propagules (2.0) followed by CAMT (1.4) and KINGD (1.1). Aromatic and Catigan Green Dwarf had the least Phytopthora propagules. Isolation of Phytophthora from the soil samples and organic debris from leaf axil was done through dilution plate and baiting method respectively using six month old Malayan Red Dwarf (MRD) nuts. Highest infection (100%) on bait nuts was also obtained in CAMT x MRD hybrid 3.5 days after inoculation. Reisolation of Phytophthora from bait nuts gave positive results. Morphological characterization of the sporangium showed considerable variation in shapes and size. More Phytophthora propagules was obtained in soil samples collected in areas previously planted with Malayan Yellow Dwarf x West African Tall (MAWA). Phytophthora palmivora is basically a soil borne pathogen but could easily be transported by wind and rainsplash, tent building ants and flying beetles.